Differential embryotoxicity of the organic pollutants in rural and urban air particles. (November 2015) - Mesquita, Sofia R.; van Drooge, Barend L.; Oliveira, Eva; Grimalt, Joan O.; Barata, Carlos; Vieira, Natividade; Guimarães, Laura; Piña, Benjamin
Abstract: Airborne particulate matter (PM) is a recognized risk factor for human populations. Here we assessed the toxic potential of the organic constituents from PM collected in urban and rural sites during warm and cold periods of 2012/2013, and fractionated into 6 size fractions. The finest PM fraction (<0.5 μm) showed the highest biological activity (dioxin-like activity and fish embryotoxicity) in all samples, and the maximal activity was observed in rural samples from the cold period. Zebrafish embryo transcriptome analysis showed a strong induction of the AhR signaling pathway correlated to PAH concentrations. Oxidative stress-related genes and pancreatic and eye-lens gene markers appeared de-regulated in embryos exposed to urban extracts, whereas exposure to rural extracts affected genes implicated in basic cellular functions. The observed effects can be directly related to air pollution-related human disorders, suggesting different potential adverse outcomes for human populations exposed to air pollution from specific sources. Graphical abstract: Highlights: Embryotoxicity of airborne organic compounds collected in urban and rural areas. Ultrafine particles (<0.5 μm) accumulated most of the observed toxicity. Strong seasonal differences in rural areas, probably linked to wood combustion. Rural and urban samples showed quantitative and qualitative differences in toxicity. At least one independent toxic modes of action especially linked to urban emissions. Abstract : Quantitative and qualitative differences in embryotoxic effects of airborne particulate matter from urban and rural areas.